Differences in Choroidal Structures Between Idiopathic and Steroid-Induced Central Serous Chorioretinopathy. (January 2019) - Izumi, Takahiko; Koizumi, Hideki; Takahashi, Yohei; Maruko, Ichiro; Sonoda, Shozo; Sakamoto, Taiji; Iida, Tomohiro
Purpose: The purpose of this article is to investigate the differences in intrachoroidal structures between eyes with idiopathic central serous chorioretinopathy (CSC) and those with steroid-induced CSC. Methods: Thirty eyes of 30 patients with idiopathic CSC and 17 eyes of 15 patients with steroid-induced CSC were studied. Cross-sectional swept-source optical coherence tomography images of eyes with idiopathic and steroid-induced CSC were retrospectively analyzed by the manual layer delineation technique and by the binarization technique. Results: The mean subfoveal choroidal thickness (SCT) was not significantly different between the eyes with idiopathic CSC (408.0 ± 106.6 µm) and those with steroid-induced (389.9 ± 105.4 µm; P = .67) CSC. Manual layer delineation showed that the mean ratio of the large choroidal vessel layer thickness to the SCT was significantly higher in eyes with idiopathic CSC (0.874 ± 0.070) than in eyes with steroid-induced CSC (0.828 ± 0.083; P = .02). The binarization method showed that the mean ratio of the luminal areas to the choroidal areas centered at the fovea was significantly higher in eyes with idiopathic CSC (0.747 ± 0.064) than in eyes with steroid-induced CSC (0.701 ± 0.046; P = .01). Conclusion: The intrachoroidal structures in steroid-induced CSC were different from those in idiopathic CSC. These findings suggest different pathophysiologic mechanisms may be involved in the pathogenesis of these 2 entities.